Former Yugoslav Republic of Macedonia : Staff Report for the 2011 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2012)
This 2011 Article IV Consultation highlights that Macedonia is poised to achieve low but positive growth under the baseline scenario of a shallow recession in the euro area. Under a downside scenario, growth would be weaker, and external financing pressures could arise. In the near term, the government would need to reduce expenditure growth to meet the 2012 deficit target. A key longer-term challenge would be to reconcile the competing objectives of higher public investment and increases in pensions and public wages while preserving low public debt and low taxes.